EVALUATION OF GUIDANCE AND COUNSELLING PRACTICES IN SCHOOLS: A CASE STUDY OF MANHYIA SUB-METROPOLIS, GHANA - Cecijoe Asiedu-Yirenkyi; Eunice Agyeiwaa Kyere; Kennedy Nyeseh Ofori , (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The study was conducted to evaluate Guidance and Counselling Services in Manhya Sub-Metropolis in the Ashanti Region of Ghana and their impact on students. The objectives of the study were to ascertain the state of Guidance and Counselling services and to identify the types of guidance services provided in the schools. In trying to accomplish this study, descriptive survey was used as the design. Two sets of questionnaires were designed for students and school-based Counsellors respectively. Data was gathered from a sample size of 310. The purposive sampling and simple random sampling techniques were employed in selecting the respondents respectively. Descriptive statistics were used in analysing the data collected. It was found that 60% of the counsellors were untrained, while about half of the schools (53.3%) did not have counselling offices. The findings also revealed that counselling and orientation were the most guidance services operating in the schools. Recommendations included the reduction of teaching periods for school-based counsellors and provision of offices for counselling sessions.